2003
DOI: 10.1074/jbc.m211997200
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Assembly Induction and Cell Migration and Invasion Inhibition by a 13-Amino Acid Fibronectin Peptide

Abstract: Fibronectin (FN) is an extracellular matrix (ECM)pro Fibronectin (FN)1 is an adhesive heterodimeric glycoprotein present in the extracellular matrix (ECM) of connective tissues in disulfide cross-linked insoluble fibrils and in the blood in dimeric soluble form. FN contains three types of homologous repeats (I-III), organized in functional domains, connected by flexible, protease-sensitive segments, which allow the binding of the molecule to ECM components (fibrin, heparin, collagen, FN, and integrin receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 50 publications
(54 reference statements)
0
21
0
2
Order By: Relevance
“…The extracellular protein fibronectin is part of the extracellular matrix and disregulated in cancer cells [20]. In correlation with the marked proliferation defects observed in Hsf2 -/-MEFs, these cells displayed an increase in fibronectin staining in immunocytochemistry experiments, as well as revealed profound remodeling of the fibronectin network (Fig.…”
Section: Fibronectin Network In Hsf2 -/-Mefsmentioning
confidence: 84%
“…The extracellular protein fibronectin is part of the extracellular matrix and disregulated in cancer cells [20]. In correlation with the marked proliferation defects observed in Hsf2 -/-MEFs, these cells displayed an increase in fibronectin staining in immunocytochemistry experiments, as well as revealed profound remodeling of the fibronectin network (Fig.…”
Section: Fibronectin Network In Hsf2 -/-Mefsmentioning
confidence: 84%
“…It was reported that loss of ECM integrity influences cellular transformation and tumorigenesis in vivo (26). Therefore, we examined whether inactivation of the VHL-ECM assembly pathway contributes to tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative evaluation of fluorescence associated with the FN-and COLL-ECM organized by control and EDS cells, was performed as previously reported (25). The fluorescent images, with the same spatial resolution and comparable light intensity, were captured by a CCD black and white TV camera mounted on a Zeiss Axiovert 10S/H fluorescence microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Human skin fibroblasts adhere in vitro through the organization of an ECM mainly composed of FN and types III, V, and VI COLLs (3,24). FN can bind to COLLs through several COLL binding sites (25), and FN binding sites in COLL molecules have been reported (26). Many data indicate the interdependence of FN and COLL network assembly; in particular, in several cell systems, the assembly of COLLs has been shown to depend on FN organization (3,27), whereas, in others, COLLs have been shown to influence FN fibrillogenesis (26,28).…”
mentioning
confidence: 99%